Travelling to India: Eliza Fay’s narrative account of her voyages - Simões-Ferreira, Isabel (2014)
Eliza Fay’s Original Letters from India (1817), initially sold to the Calcutta Gazette to pay off her debts, aroused the curiosity and interest of Edward M. Forster, while he was doing research for his best-selling novel, A Passage to India. In his own words, “Eliza Fay is a work of art.” (apud Fay 7) The value of E. Fay’s travelogue, comprising not one, but three voyages to India (in 1779, 1784, 1796) can be easily explained if we take into account the scope of its geographical coverage, the hardships of its historical context (the political chaos brought about by the fall of the Mughal empire and the consolidation of the British rule in the Indian subcontinent) and the heroism of the first person-narrator that emerges behind the descriptive sketches and the scenes of adversity and imminent danger. Thus the current analysis will focus on the E. Fay’s adventurous mode of narrating, e.g., the discursive situatedness of the traveller visà- vis the Other(s) (European and non-European peoples and loci) and the constraints imposed by the patriarchal idealization of the domestic Woman and their alleged feebleness.